2014
DOI: 10.21101/cejph.a3903
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Characteristics of the Population Living in Roma Settlements and Their Association with Health and Health-Related Behaviour

Abstract: SUMMARYBackground: The aim of this study was to compare socioeconomic characteristics of the Roma population living in Roma settlements with the majority population. Moreover, it was aimed to assess socioeconomic differences in health and health-related behaviour within the population living in Roma settlements.Methods: Data from the cross-sectional HepaMeta study conducted in Slovakia in 2011 were used. The sample consisted of 452 Roma (mean age = 34.7; 35.2% men) and 403 non-Roma (mean age = 33.5; 45.9% men)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
5
27
0
Order By: Relevance
“…Compared with Roma women, Slovak/other European women generally have greater economic resources to purchase consumer products that may contain PFASs. 57 This interpretation is consistent with results from other studies that have observed positive associations between income and maternal PFAS concentrations. 25, 29 …”
Section: Discussionsupporting
confidence: 92%
“…Compared with Roma women, Slovak/other European women generally have greater economic resources to purchase consumer products that may contain PFASs. 57 This interpretation is consistent with results from other studies that have observed positive associations between income and maternal PFAS concentrations. 25, 29 …”
Section: Discussionsupporting
confidence: 92%
“…Sexual behaviour may be affected not only by the use of alcohol or other substances but also by socio-economic status or psychosocial determinants, which should be explored further. Nevertheless, as pointed out in the study of Madarasova Geckova et al (2014) “the deteriorating effect of living in Roma settlement on health and health related behaviour seems to be immense regardless differences in SE characteristics or living conditions within the settlement population” [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Roma population living in separated and segregated settlements can be considered as the most disadvantaged group, regarding the poor socioeconomic position, living and working conditions, segregation and social exclusion [ 3 , 4 , 5 , 6 , 7 , 8 ]. Several studies have revealed a range of barriers for Roma in accessing health services [ 9 , 10 , 11 ], including sexual and reproductive health services [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible causes of this phenomenon is the lower compliance to treatment and lower rate of successfully completed treatment by Roma patients (21% dropout compared to 0% dropout in the control group). Lower socioeconomic standard and other factors associated with segregation in marginalized communities are also possible causes of lower treatment efficacy [ 12 ]. Significant portion of Roma patients in our study came from such settlements.…”
Section: Discussionmentioning
confidence: 99%